2021
DOI: 10.1142/s0219455421501212
|View full text |Cite
|
Sign up to set email alerts
|

Spall Behaviors of Metaconcrete: 3D Meso-Scale Modelling

Abstract: Spalling is a typical tensile fracture phenomenon due to insufficient tensile strength of concrete. Concrete structure might experience severe spall damage at the rear surface of the structure owing to reflected tensile stress wave induced by impulsive load. In recent years, metaconcrete consisting of engineered aggregates has attracted attentions as metaconcrete exhibits extraordinary wave-filtering characteristics. Metaconcrete can be used to attenuate stress wave generated by impulsive load and hence possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…This study extends the previous work reported by the authors [24]. The latter study found that although the stress wave amplitudes were reduced owing to the wave propagation mitigation effect by NEA in metaconcrete material, the spalling damage was not necessarily less severe compared to NC without NEA because mixing NEA reduced the concrete strength.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study extends the previous work reported by the authors [24]. The latter study found that although the stress wave amplitudes were reduced owing to the wave propagation mitigation effect by NEA in metaconcrete material, the spalling damage was not necessarily less severe compared to NC without NEA because mixing NEA reduced the concrete strength.…”
Section: Introductionsupporting
confidence: 89%
“…All components in the specimen are simulated by the constant stress solid element. Mesh convergence test and model calibration have been conducted and reported in Jin et al [23,24], which is not repeated here. The mesh size of 0.5 mm after conducting mesh convergence test is determined and used in this study [23,24].…”
Section: D Meso-scale Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Gao et al (2018) numerically studied wave attenuation performance of metaconcrete slab under two-dimensional plane wave and found that the metaconcrete slab could effectively weaken the mechanical wave and better protect the concrete mortar. Jin et al (2020Jin et al ( ,2021) conducted analytical derivation and numerical simulation to study the dynamic respones of metaconcrete structure under explosion loading and the impact of elastic modulus and thickness of coating, aggregates kinds on the anti-explosion behavior of metaconcrete was investigated. It was found that the engineered aggregates can mitigate the damaged of metaconcrete structural against blast loading.…”
Section: Introductionmentioning
confidence: 99%